‘Trap Life’: The psychosocial underpinnings of street crime in inner-city London - Reid, Ebony (The British journal of criminology, 2023)
This article explores urban men’s involvement in the drug economy, examining the conditions in which they become ‘trapped’ in difficult lifeworlds and identities. Through an ethnographic exploration of what disadvantaged urban men term ‘trap life’, this article demonstrates how different ‘trapper’ identities, enacted to manage economic, social and psychological vulnerability, allows an understanding of the varied motivations to take part in criminality and violence. Whilst the terms ‘dangerous’, ‘pathological’ and ‘criminal’ are deployed to account for street lifestyles, such stereotypical imagery with roots in history, media, political discourse and policing practices, downplays the humanity of men living on the margins of society and neglects their version of reality. Far from being exclusively violent perpetrators, urban men are especially vulnerable as they are trapped in a never-ending existential crisis, which prevents successful transitions into mainstream life. I demonstrate that the issue of violence and the 21st century drug business must be placed in broader psychosocial contexts to provide a better understanding and perhaps one-day inform therapeutic and other practice interventions specifically tailored for those seeking to exit ‘trap life’.